'I know It When I See It': On Academic Plagiarism, and How to Assess It. (July 2020) - Ramalho, Ana; Silva, Marta Santos
In the academic context, plagiarism is usually seen as an ethical offence, the boundaries and definition of which are often unclear. However, in some countries, plagiarism is also a legal wrong, amounting to copyright infringement. This article proposes a test for assessing plagiarism of academic works. The test is based on the law and jurisprudence of a particular country, Portugal, where plagiarism is framed as copyright infringement. Article 196 of the Portuguese Copyright Law sets four elements that must be fulfilled for a finding of plagiarism: There must be a protected work; the alleged plagiarist must have used a partial or total reproduction of that work; the alleged plagiarist must have failed to attribute the authorship of the work to its rightful creator; and the work of the alleged plagiarist must lack its own individuality. The authors argue that, even if the law of a particular country does not frame plagiarism as a legal offence, these elements should be part of a test to be adopted and applied by academic institutions for the sake of legal certainty.